Investigating the Effect of Mobile Apps on Student’s Motivation and Achievement in Motor Vehicle Mechanic Work - Ike, Joshua Onyedikachi; Ariyo, Samson Oluwatimilehin; Olaitan, Olawale Opeyemi (Middle Eastern Journal of Research in Education and Social Sciences, 2020)
Purpose: The study was carried out to investigate the effect of mobile apps on students’ achievement in petrol engine maintenance work in technical colleges in Enugu State, Nigeria. Approach/Methodology/Design: The study adopted quasi-experimental design and was carried out in Enugu State, Nigeria. The population for the study was 170 NTC II students. The sample size for the study was 40 motor vehicle mechanics work NTC II students who have any mobile technologies (Smart phones) participated in the experimental group and were selected using purposive sampling technique. The instrument for data collection was motor vehicle mechanic work achievement test (MWMWAT). The data collected were analyzed using mean, to answer the research questions while ANCOVA was used to test the hypothesis. Three research questions were answered, while one null hypothesis formulated were tested at 0.05 level of significance. Findings: The study revealed that students taught petrol vehicle maintenance works with mobile apps had a higher mean achievement score than those students taught using conventional teaching aids in the achievement test. There was a significant difference between the mean achievement scores of students taught with mobile apps and those taught with conventional teaching aids in motor vehicle mechanics work trade. Practical Implications: The study will contribute positively to the understanding of using mobile apps to increase students’ motivation and academic achievement. Originality/value: This study innovates in examining the use of mobile apps by motor vehicle mechanic work teachers in improving the motivation and academic achievement of students.